1985
DOI: 10.1002/tera.1420320306
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of malformations of the embryonic neural axis induced by in vitro hyperglycemic conditions

Abstract: Neural tube defects are the most common malformations associated with diabetic pregnancies. Although the teratogenic effects of excess glucose have been investigated in in vivo and in vivo studies, a cellular basis for neural tube defects has not been elucidated. We used rat embryo culture to study the organogenesis period of development, with excess d-glucose added to the serum medium to induce neural tube anomalies. Light and electron microscopic examination of control 12-day-old embryos grown 48 hours in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…15 It has also been hypothesized that hyperglycemia leads to release of free radicals from the influx of glucose across injured cell and mitochondrial membranes, overwhelming the immature fetal free radical scavenging enzymes. These excess free radicals can be teratogenic either directly or through a chain of events including enhanced lipid peroxidation and prostaglandin imbalance, ultimately leading to disruption in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has also been hypothesized that hyperglycemia leads to release of free radicals from the influx of glucose across injured cell and mitochondrial membranes, overwhelming the immature fetal free radical scavenging enzymes. These excess free radicals can be teratogenic either directly or through a chain of events including enhanced lipid peroxidation and prostaglandin imbalance, ultimately leading to disruption in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the susceptibility of rat embryos to direct exposure to high glucose concentrations has been clearly demonstrated by the use of the whole-embryo culture. However, the susceptibility of the embryos in different laboratories was markedly different: e.g., Cockroft and Coppola [13] observed no malformed embryos until the added glucose concentrations were in excess of 50 mM, whereas Reece et al [15] and Pinter et al [44] reported malformed embryos following exposure to only 19.4 mM glucose added to normal serum. These data suggest that a number of factors other than hyperglycemia play a role in streptozotocininduced diabetes embryotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, embryo culture has been used as a simplified method to discriminate between them. During these studies several agents have been shown to be teratogenic: hyperglycemia (obtained by adding very high and unrealistic concentrations of glucose to the culture medium) [13][14][15], ketone bodies [16][17][18][19], and somatomedin inhibitors [18,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…There was a differential dose-dependent effect between axial rotation and neural tube closure defects. Reece (Reece et al, 1985) studied ultrastructural malformations of the embryonic neural axis under hyperglycemic culture conditions and showed significant cytoarchitectural alterations in the neuroepithelium. Goldman (Goldman et al, 1985) presented data suggesting that the mechanisms of the glucose-dependent teratogenic effects were mediated by a functional deficiency of arachidonic acid at a critical period of organ differentiation.…”
Section: Introductionmentioning
confidence: 99%